Role of the Armed Forces in Military Operations Other Than War in Managing Natural Disasters - Anthony Wende; Jonni Mahroza; Rizerius E. Hadisancoko; Sherif O. Aremu (CV. AFDIFAL MAJU BERKAH, 2023)
The study analysis the role of the Armed Forces in MOOTW in managing natural disasters in a country effectively. The method utilized is the diary research method that involved analysis of creditable documents, media reports and internet reports on the role the military played in assisting government in addressing disasters. The results indicated that there are climates change threats in form of natural disasters affecting the globe of recent. Hence, it was recommended that national government could involve their Armed Forces in managing the natural disasters under the umbrella of MOOTW. The Armed Forces should operate to aid the governmental agencies responsible for the management of natural disasters in the country. This could assist to bring succour to the victims of the disasters and as well enhance the government profile among its citizens. It concludes by assessing the role Armed Forces could played in support to disasters management by operating under the MOOTW to assists the disasters agencies to bring succour to the victims. It then discussed the type of units that could be employed by the various Services of the Armed Forces and dwelled on the inter-agencies’ cooperation for smooth conduct of the operations in aid to disasters victims. Finally, it was view that the use of the Armed Force under MOOTW in managing natural disasters would be a welcome development if all nations decided to incorporates the military in disasters management plan. Hence, nations should consider employing part of its Armed Forces in future disaster management issue that could threaten the citizens of the nation